Solar cell and manufacturing method thereof

JP2025035932APending Publication Date: 2025-03-14KANAZAWA UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023143295
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、安定して高い出力特性を実現することが可能な太陽電池と、その製造方法を提供することできる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035932000001_ABST
    Figure 2025035932000001_ABST
Patent Text Reader

Abstract

To provide solar cells that can achieve stable and high output characteristics.SOLUTION: A solar cell according to the present invention includes a laminate in which an electron transport layer 102, a power generation layer, and a hole transport layer 104 are stacked in this order, or in which the hole transport layer 104, a power generation layer, and an electron transport layer 102 are stacked in this order, a negative electrode layer connected to the electron transport layer 102, and a positive electrode layer connected to the hole transport layer 104. The power generation layer has a perovskite crystal structure and contains Rb, and the average grain size of the crystal grains contained in the power generation layer is 350 nm or more.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solar cell and a method for manufacturing the same. [Background technology]

[0002] In recent years, organic solar cells have been developed using films of organic materials with a perovskite structure. The perovskite structure is a cubic crystal structure expressed by the general formula ABX3. Different atoms or molecules are arranged at the vertices of the cube (A site), the center of each face of the cube (B site), and the center of the cube (X site). Organic materials such as CH3NH3 and CH5N2 are used for the A site.

[0003] By using a film in which part of the organic material in the A site is replaced with an inorganic material such as Rb as the power generation layer, it is possible to increase the stability of the solar cell against moisture, light, heat, etc. Such a film is generally obtained by mixing the materials to be contained in a liquid state, applying it to a base substrate, and drying it (Non-Patent Document 1).

[0004] However, the film obtained by this method is composed of small crystal grains and contains many grain boundary regions, making it difficult to improve the efficiency of carrier conduction. Therefore, even if this film is used as the power generation layer of a solar cell, it is thought that it will be difficult to significantly improve the output characteristics. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Park, IJ, Seo, S., Park, MA, Lee, S., Kim, DH, Zhu, K., Shin, H., Kim, JY (2017). Effect of rubidium incorporation on the structural, electrical, and photovoltaic properties of methylammonium lead iodide-based perovskite solar cells. ACS Appl Mater Interfaces, 48, 41898-41905. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a solar cell capable of achieving stable high output characteristics, and a method for manufacturing the same. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention employs the following means.

[0008] (1) A solar cell according to one embodiment of the present invention includes a laminate in which an electron transport layer, a power generation layer, and a hole transport layer are stacked in this order, or in which a hole transport layer, a power generation layer, and an electron transport layer are stacked in this order, an anode layer connected to the electron transport layer, and a cathode layer connected to the hole transport layer, wherein the power generation layer has a perovskite crystal structure and contains Rb, and the average grain size of crystal grains contained in the power generation layer is 350 nm or more.

[0009] (2) The solar cell according to the above (1) may further include an Rb supply layer made of a halide of Rb between the power generation layer and the electron transport layer or between the power generation layer and the hole transport layer.

[0010] (3) A method for manufacturing a solar cell according to one embodiment of the present invention includes a first Rb supply layer formation step of forming a first Rb supply layer made of a Rb halide on an electron transport layer or a hole transport layer, a perovskite layer formation step of forming a perovskite layer having a perovskite type crystal structure on the first Rb supply layer, and a heating step of heating the first Rb supply layer and the perovskite layer.

[0011] (4) In the method for producing a solar cell described in (3) above, the first Rb supply layer is preferably formed by vapor deposition.

[0012] (5) The method for manufacturing a solar cell according to either (3) or (4) above may further include a second Rb supply layer forming step between the perovskite layer forming step and the heating step, and in the second Rb supply layer forming step, a second Rb supply layer made of a halide of Rb may be formed on the perovskite layer.

[0013] (6) A method for manufacturing a solar cell according to another embodiment of the present invention includes a perovskite layer forming step of forming a perovskite layer having a perovskite type crystal structure on an electron transport layer or a hole transport layer, a second Rb supply layer forming step of forming a second Rb supply layer made of a Rb halide on the perovskite layer, and a heating step of heating the second Rb supply layer and the perovskite layer.

[0014] (7) In the method for producing a solar cell according to either of the above (5) or (6), the second Rb supply layer is preferably formed by vapor deposition. Effect of the Invention

[0015] According to the present invention, it is possible to provide a solar cell capable of achieving stable high output characteristics, and a method for manufacturing the same. [Brief description of the drawings]

[0016] [Figure 1]1 is a side view of a solar cell according to one embodiment of the present invention; [Diagram 2] FIG. 2 is a diagram showing the crystal structure of a power generation layer that constitutes a solar cell. [Diagram 3] 1(a) to 1(d) are perspective views of the power generation layer during the formation process. [Figure 4] FIG. 11 is a perspective view of the power generation layer during another formation process. [Diagram 5] FIG. 11 is a perspective view of the power generation layer during another formation process. [Figure 6] 1( a ) and 1 ( b ) are diagrams illustrating the relationship between the size of the crystal grains that make up the power generation layer and the output characteristics of the solar cell. [Figure 7] 1 is an enlarged SEM image of a portion of the power generation layer of Comparative Example 1. [Figure 8] 1 is an enlarged SEM image of a portion of the power generation layer of Example 1. [Figure 9] 1(a) is an enlarged SEM image of a part of the power generation layer of Example 1. (b) is an image obtained by subjecting the power generation layer of Example 1 to EDX analysis. [Figure 10] 1 is a graph showing X-ray diffraction patterns for the power generation layers of Comparative Example 1 and Example 1. [Figure 11] 1 is a graph showing output characteristics of solar cells provided with power generation layers of Comparative Example 1 and Example 1. [Figure 12] 1 is a graph showing the time change in output characteristics when exposed to light for solar cells including the power generation layers of Comparative Example 1 and Example 1. [Figure 13] 1 is a graph showing the change over time in output characteristics when heated for solar cells including the power generation layers of Comparative Example 1 and Example 1. [Figure 14] 13 is an enlarged SEM image of another part of the power generation layer of Comparative Example 2. [Figure 15] 1 is an enlarged SEM image of a portion of the power generation layer of Example 2. [Figure 16] 13 is an enlarged SEM image of a portion of the power generation layer of Comparative Example 3. [Figure 17] 13 is an enlarged SEM image of a portion of the power generation layer of Example 3. [Figure 18] 1 is a graph showing output characteristics of solar cells provided with power generation layers of Comparative Example 3 and Example 3. [Figure 19] 1 is a graph showing the distribution of energy conversion efficiency corresponding to the thickness of the first Rb supply layer. [Figure 20] 1 is a graph showing output characteristics of solar cells provided with the power generation layers of Examples 1, 4, and 5. [Figure 21] 1 is a graph showing output characteristics of solar cells provided with power generation layers of Comparative Example 4 and Example 6. [Figure 22] 1 is a graph showing the distribution of energy conversion efficiency corresponding to the thickness of the perovskite layer. [Figure 23] 1 is a graph showing output characteristics of solar cells provided with the power generation layers of Examples 1 and 7 to 9. [Figure 24] 1 is a graph showing the distribution of energy conversion efficiency corresponding to the heating temperature in a heating step for forming a power generation layer. [Diagram 25] 1 is a graph showing the distribution of energy conversion efficiency versus heating time in a heating step for forming a power generation layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The solar cell according to the embodiment of the present invention and its manufacturing method will be described in detail below with reference to the drawings. Note that the drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the characteristics easier to understand, and the dimensional ratios of each component may not necessarily be the same as in reality. In addition, the materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and may be appropriately modified and implemented within the scope of the present invention.

[0018] FIG. 1 is a side view of a solar cell 100 according to one embodiment of the present invention. The solar cell 100 mainly includes a substrate 101, an electron transport layer 102, a power generation layer 103, a hole transport layer 104, two electrode layers (anode layer and cathode layer) 105, and an anode layer 106. FIG. 1 illustrates a case in which the electron transport layer 102, the power generation layer 103, and the hole transport layer 104 are stacked in this order on the substrate 101, and the electrode layer 105 contacts the electron transport layer 102 via the anode layer 106, and the electrode layer 105 contacts the hole transport layer 104. The positions of the electron transport layer 102 and the hole transport layer 104 may be interchanged, and the positions of the anode layer 106 and the cathode layer 105 may be interchanged.

[0019] The substrate 101 is not particularly limited as long as it supports the structure composed of the above-mentioned layers. The substrate 101 is preferably a transparent conductive substrate with excellent light transmittance, and more preferably has a visible light transmittance of 90% or more. The substrate 101 is also preferably flexible. Examples of materials constituting the substrate 101 include glass and plastic film. Examples of resins constituting the plastic film include polyethylene terephthalate and polyethylene naphthalate.

[0020] The power generation layer 103 is a layer (photoelectric conversion layer) that receives light and generates power. The power generation layer 103 is made of a material having a perovskite structure. FIG. 2 is a diagram showing a schematic diagram of a perovskite type crystal structure that constitutes the power generation layer 103. The perovskite structure is a cubic crystal structure expressed by the general formula ABX3. Different atoms or molecules are arranged at the vertices (A sites) 103A of the cube, the centers (X sites) 103X of each face of the cube, and the center (B site) 103B of the cube. For example, materials such as CH3NH3 and CH5N2 are used at the A site. For example, materials such as Pb, Sn, and Ge are used at the B site. For example, materials such as I, Cl, and Br are used at the X site.

[0021] The power generation layer 103 contains Rb (rubidium). By containing Rb, the average grain size of the crystal grains constituting the power generation layer 103 becomes larger than when Rb is not contained. The average grain size of the crystal grains changes in proportion to the concentration of Rb. The average grain size of the crystal grains is 350 nm or more, preferably 400 nm or more, and more preferably 500 nm or more. From the viewpoints of manufacturing and appearance, the average grain size of the crystal grains may be, for example, 1000 nm or less. By forming the power generation layer 103 with large crystal grains, the content (volume ratio) of the crystal grain boundaries is reduced. Therefore, deterioration due to the intrusion of environmental factors such as moisture, light, and heat can be suppressed, and the carrier conductivity can be maintained high.

[0022] The power generation layer 103 may have an RbX layer containing a halide of Rb represented by RbX formed on at least one of the electron transport layer 102 side and the hole transport layer 104 side. X may be I, Br, Cl, or the like. In this case, the thickness of the RbX layer is not particularly limited, but is preferably 5 nm or more and 10 nm or less. In order to maintain the cubic perovskite structure, it is preferable that the amount of Rb that enters the power generation layer 103 is small.

[0023] The electron transport layer 102 is a layer that collects electrons generated in the power generation layer 103 and efficiently transports them toward the negative electrode layer 106. Examples of materials constituting the electron transport layer 102 include inorganic materials such as zinc oxide, titanium oxide, tin oxide, niobium oxide, and aluminum oxide, as well as inorganic materials such as PCBM and fullerene C. 60 Examples of n-type semiconductors include organic materials such as those mentioned above.

[0024] The hole transport layer 104 is a layer that collects holes generated in the power generation layer 103 and efficiently transports them toward the positive electrode layer 105. Examples of materials constituting the hole transport layer 102 include p-type semiconductors such as inorganic materials such as nickel oxide, copper iodide, copper oxide, and copper sulfide, and organic materials such as Spiro-OMeTAD, PTAA, and PEDOT:PSS (a composite of poly(3,4-ethylenedioxythiophene) (PEDOT) and polystyrene sulfonic acid (PSS)).

[0025] The electrode layer 105 is made of a conductive material such as a metal such as gold, silver, or aluminum, or an organic conductive ink such as PEDOT:PSS, etc. The negative electrode layer 106 is made of a conductive material such as fluorine-doped tin oxide (FTO), indium tin oxide (ITO), indium zinc oxide (IZO), aluminum zinc oxide (AZO), zinc oxide, tin oxide, titanium oxide, graphene, etc.

[0026] At least one of between the power generating layer 103 and the electron transport layer 102 and between the power generating layer 103 and the hole transport layer 104 may have an Rb supply layer (not shown) containing a halide of Rb represented by RbX. X may be I, Br, Cl, or the like. In this case, the thickness of the RbX supply layer is more preferably 5 nm or more and 10 nm or less.

[0027] The method for manufacturing the solar cell 100 of this embodiment includes a laminate formation step of forming a laminate consisting of the electron transport layer 102, the power generation layer 103, and the hole transport layer 104 on the substrate 101, and an electrode formation step of forming electrodes (electrode layer 105, anode layer 106) connected to the hole transport layer 104 and the electron transport layer 102. For example, the layers are formed (laminated) on one surface 101a of the substrate in the order of the electron transport layer 102, the power generation layer 103, and the hole transport layer 104, or the hole transport layer 104, the power generation layer 103, and the electron transport layer 102, and processed into a predetermined shape, and the electrode layer 105 and the anode layer 206 are formed so as to be in contact with the hole transport layer 104 and the electron transport layer 102, respectively, to manufacture the solar cell 100.

[0028] Furthermore, the method for manufacturing the solar cell 100 of this embodiment mainly includes an Rb supply layer forming step, a perovskite layer forming step, and a heating step in the process of forming the power generating layer 103. Figures 3(a) to (d), 4, and 5 are diagrams for explaining the state of the power generating layer 103 during the formation process.

[0029] (First Rb supply layer formation process) As shown in FIG. 3(a), a first Rb supply layer (Rb supply layer) 107 containing a halide of Rb represented by RbX is formed on the electron transport layer 102 or the hole transport layer 104. X can be I, Br, Cl, or the like. From the viewpoint of efficiently supplying Rb to the perovskite layer 108 laminated thereon, the thickness of the first Rb supply layer 107 is set to 5 nm or more, 10 nm or less. under It is preferable that the thickness of the first Rb supply layer 107 is less than 5 nm. If the thickness of the first Rb supply layer 107 is less than 5 nm, RbX particles are scattered, making it difficult to uniformly supply Rb to the entire surface of the contacting perovskite layer 108. If the thickness of the first Rb supply layer 107 is more than 10 nm, the portion far from the contact surface with the perovskite layer 108 remains without contributing to the supply of Rb.

[0030] The method for forming the first Rb supply layer 107 is not particularly limited, and for example, a vapor deposition method (chemical vapor deposition method, physical vapor deposition method) or a liquid coating method can be used. However, it is preferable to form the first Rb supply layer 107 by using a physical vapor deposition method, particularly a thermal vapor deposition method which is a type of physical vapor deposition method, because better characteristics can be obtained. -4 In a space (chamber) under reduced pressure of atm or less, raw material powder containing RbX is heated by an Al2O3 coil through which a current of about 12 to 16 A is passed, and is adhered to the surface of the electron transport layer 102 or the hole transport layer 104. Another method is to collide a target material containing RbX with ions of argon or the like in a space (chamber) under reduced pressure, scattering the RbX particles, and depositing them on the surface of the electron transport layer 102 or the hole transport layer 104.

[0031] As the liquid application method, spin coating is preferably used, but other application methods such as bar coating, roll coating, spray coating, dip coating, and screen printing may also be used.

[0032] (Perovskite layer formation process) 3(b), a perovskite layer 108 including crystal grains having a perovskite structure is formed on the first Rb supply layer 107. The thickness of the perovskite layer 108 is preferably 250 nm or more from the viewpoint of obtaining a high output, and is preferably 850 nm or less from the viewpoint of uniformly supplying (distributing) Rb throughout the perovskite layer 108, and more preferably about 450 nm. The method for forming the perovskite layer 108 is not particularly limited, but it is preferable to use a liquid coating method (such as a spin coating method).

[0033] (Heating process) The first Rb supply layer 107 and the perovskite layer 108 are heated. The heating temperature is preferably 120° C. or more and 140° C. or less, and most preferably 140° C. The heating time is preferably 30 minutes or more and 45 minutes or less, and most preferably 45 minutes. By this heating, as shown in FIG. 3(c), RbX of the first Rb supply layer 107 is supplied into the perovskite layer 108. More specifically, of the supplied RbX, only Rb enters into the crystal structure (basic skeleton of the crystal structure) constituting the perovskite layer 108 or between the crystal structures (intercalated (heated penetration)), and X is released to the outside of the perovskite layer 108.

[0034] During the heating step, adjacent crystal particles bond (integrate) with each other, so that the power generation layer 103 is composed of larger crystal particles than before Rb is supplied, as shown in Fig. 3(d). The grain size of the crystal particles is enlarged to about 5 to 10 times that before Rb is supplied. When the first Rb supply layer 107 is thick or the perovskite layer 108 is thin, Rb may not be completely supplied (consumed), and the first Rb supply layer 107 may remain. However, the remaining first Rb supply layer 107 does not affect the characteristics of the solar cell 100.

[0035] (Second Rb supply layer formation process) Between the power generation layer forming step and the heating step, as shown in FIG. 4, a second Rb supply layer (Rb supply layer) 109 containing a halide of Rb represented by RbX may be further formed on the perovskite layer 108 (the side opposite to the substrate 101). Examples of X include I, Br, Cl, and the like. For the same reasons as for the first Rb supply layer 107, the thickness of the second Rb supply layer 109 is preferably 5 nm or more and 15 nm or less, and most preferably 10 nm. The method for forming the second Rb supply layer 109 is the same as the method for forming the first Rb supply layer 107. When the second Rb supply layer 109 is thick or the perovskite layer 108 is thin, Rb may not be completely supplied (consumed), and the second Rb supply layer 109 may remain, but the remaining second Rb supply layer 109 does not affect the characteristics of the solar cell 100.

[0036] Rb of the first Rb supply layer 107 is supplied from the lower surface (surface on the substrate 101 side) 108a of the perovskite layer 108, but there is a limit to the supply range, and it is difficult to uniformly supply Rb to an area that is too far from the lower surface 108a. On the other hand, Rb of the second Rb supply layer 109 is supplied from the upper surface (surface opposite to the substrate 101) 108b of the perovskite layer 108. Therefore, Rb of the second Rb supply layer 109 can be supplied from the upper surface 108b of the perovskite layer 108 to an area that is too far from the lower surface 108a and to which Rb of the first Rb supply layer 107 is not supplied. A configuration that can supply Rb from both the upper and lower sides of the perovskite layer 108 in this way is effective when the perovskite layer 108 is thick.

[0037] Alternatively, the second Rb supply layer 109 may be formed without forming the first Rb supply layer 107, and Rb may be supplied to the perovskite layer 108 only from the upper side (the side opposite to the substrate 101). In this case, the method for manufacturing the solar cell 100 mainly includes a perovskite layer forming step, a second Rb supply layer forming step, and a heating step in the process of forming the power generating layer 103. Fig. 5 is a diagram showing a state in which the second Rb supply layer 109 is formed on the upper surface 108b of the perovskite layer after the above-mentioned perovskite layer forming step.

[0038] 6(a) and (b) are cross-sectional views each showing a schematic configuration of a power generation layer 103 manufactured by a different manufacturing method. The power generation layer 103 in FIG. 6(a) is obtained by a conventional manufacturing method in which a liquid of Rb to be contained is mixed with a liquid of another material, applied to a base substrate, and dried. The power generation layer 103 in FIG. 6(b) is obtained by the manufacturing method of the present embodiment described above, that is, by forming an Rb supply layer by vapor deposition, applying a liquid of another material thereon, and heating. The crystal grain size of the power generation layer 103 in this embodiment is larger than that of the conventional power generation layer 103 due to the difference in the Rb supply process.

[0039] Electrons E and holes H generated in the power generation layer 103 by irradiation with sunlight L or the like flow toward the negative electrode layer 106 and the electrode layer 105, respectively, but some of them are trapped at the crystal grain boundaries 103C that exist in the flow path. The trapped electrons E and holes H recombine, so the number of electrons E that reach the negative electrode layer 106 and the number of electrons E that reach the electrode layer 105 decrease, resulting in a loss of output current. In the power generation layer 103 of this embodiment shown in FIG. 6(b), the grain size of the crystal grains is large, and the distribution density (volume density) of the crystal grain boundaries 103C is low. Therefore, by applying the power generation layer of this embodiment, it is possible to reduce carriers trapped and recombined at the crystal grain boundaries 103C, suppress the loss of output current due to the decrease in carriers that reach the electrodes, and improve the output characteristic (PCE) of the solar cell.

[0040] As described above, according to the method for manufacturing the solar cell of the present embodiment, in the power generation layer formation step, the perovskite layer 108 is brought into contact with at least one of the first Rb supply layer 107 and the second Rb supply layer 109 and heated, whereby Rb can be intercalated into the perovskite layer 108 and the crystal grain size of the perovskite layer 108 can be increased.

[0041] As a result, in the solar cell 100 of this embodiment, the distribution density of the crystal grain boundaries in the power generation layer 103 is low, which reduces the loss of output current caused by carrier recombination at the crystal grain boundaries and improves the output characteristics. In addition, in the solar cell 100 of this embodiment, the distribution density of the crystal grain boundaries in the power generation layer 103 is low, which prevents the intrusion of environmental factors such as moisture, light, and heat, thereby suppressing deterioration of the power generation layer 103 and achieving stable output characteristics. EXAMPLES

[0042] The effects of the present invention will be more clearly understood by the following examples. Note that the present invention is not limited to the following examples, and can be modified as appropriate without departing from the spirit and scope of the present invention.

[0043] Example 1 Using the method for manufacturing a solar cell according to the above embodiment, a solar cell was manufactured as shown in Fig. 1. The main materials for the layers constituting the solar cell were as follows. Substrate: Glass Negative electrode layer: FTO Electron transport layer:TiO2 Power generation layer: CH3NH3PbI3(MAPbl3)+Rb Hole transport layer: Spiro-OMeTAD Positive electrode layer: Gold

[0044] The formation of the power generation layer was carried out on the substrate on which the electron transport layer had been formed, by the following procedure. First, a first Rb supply layer containing RbI was formed on the electron transport layer by using a thermal evaporation method. -4 In a chamber under reduced pressure of 1 atm, raw material powder containing RbI was heated by an Al2O3 coil through which a current of 14 A was passed, and the raw material powder was attached to the surface of the electron transport layer to form a first Rb supply layer with a thickness of 10 nm.

[0045] Next, a perovskite layer (450 nm thick) made of CH3NH3PbI3 was formed on the first Rb supply layer by spin coating. Next, the workpiece on which the perovskite layer was formed was placed in a heating vessel, and the first Rb supply layer and the perovskite layer were heated at 140°C for 45 minutes to form a power generation layer.

[0046] (Comparative Examples 1 to 4) Except for not forming the first Rb supply layer, a solar cell was manufactured in the same manner as in Example 1. As the power generation layer, a perovskite layer of CH3NH3PbI3 not containing Rb was formed directly on the electron transport layer.

[0047] Example 2 A solar cell was manufactured in the same manner as in Example 1, except that the first Rb supply layer was formed by spin coating (liquid method). In the first Rb supply layer formation step, a liquid containing 0.3 M RbI was applied onto the electron transport layer by spin coating at 4000 rpm for 30 seconds. 10 seconds before the end of application, 600 μL of chlorobenzene was added. The substrate after application was dried at 100° C. for 10 minutes.

[0048] Example 3 Except for not forming the first Rb supply layer and forming the second Rb supply layer, a solar cell was manufactured in the same manner as in Example 1. The second Rb supply layer was formed under the same conditions as the first Rb supply layer in Example 1.

[0049] (Examples 4 and 5) Solar cells were produced in the same manner as in Example 1, except that the thickness of the first Rb supply layer was set to 5 nm and 15 nm.

[0050] Example 6 Except for forming the second Rb supply layer together with the first Rb supply layer, a solar cell was manufactured in the same manner as in Example 1. The second Rb supply layer having a thickness of 10 nm was formed under the same conditions as the first Rb supply layer in Example 1.

[0051] (Examples 7, 8, and 9) Solar cells were produced in the same manner as in Example 1, except that the thickness of the perovskite layer was changed to 250 nm, 650 nm, or 850 nm.

[0052] (Examples 10, 11, and 12) Solar cells were produced in the same manner as in Example 1, except that the heating temperatures for the first Rb supply layer and the perovskite layer were set to 100°C, 120°C, and 150°C.

[0053] (Examples 13, 14, and 15) Solar cells were produced in the same manner as in Example 1, except that the heating times for the first Rb supply layer and the perovskite layer were changed to 15 minutes, 30 minutes, and 60 minutes.

[0054] [Surface observation 1] The surfaces of the power generation layers formed in Example 1 and Comparative Example 1 were observed. 6 nm 2 The SEM images were taken in a region of (2200 nm × 1600 nm). In the power generation layer of Comparative Example 1, the crystal grain size was about 100 to 200 nm, whereas in the power generation layer of Example 1, the crystal grain size was about 500 to 600 nm, and the crystal size was significantly larger. The larger crystal grain size in the power generation layer of Example 1 is believed to be due to Rb being intercalated.

[0055] [EDX analysis] An EDX analysis was performed on the surface of the power generation layer of Example 1. FIG. 7 nm 2 FIG. 9(b) is an SEM image of an area of ​​(4800 nm × 3600 nm) in the power generation layer of Example 1. FIG. 9(b) is an image of the Rb distribution obtained by EDX analysis in the same area of ​​the power generation layer of Example 1. Comparing the two images, it can be seen that most of the intercalated Rb is distributed along the grain boundaries in the power generation layer. In the crystal structure of the power generation layer, the concentration of Rb distributed at the grain boundaries is higher than the concentration of Rb distributed within the crystal grains.

[0056] [XRD analysis] X-ray diffraction analysis was performed on the power generation layers of Example 1 and Comparative Example 1. FIG. 10 is a graph showing the X-ray diffraction patterns obtained from these power generation layers. The X-ray diffraction pattern of Example 1 has a peak at the same position as the X-ray diffraction pattern of Comparative Example 1. Furthermore, the X-ray diffraction pattern of Example 1 has a peak in the diffraction angle range of 12 to 13° that is not present in the X-ray diffraction pattern of Comparative Example 1. From these results, it can be seen that in the power generation layer of Example 1, Rb is intercalated while maintaining the same basic skeleton of the perovskite structure of CH3NH3PbI3 as the power generation layer of Comparative Example 1.

[0057] [Evaluation of output characteristics 1] The solar cells including the power generation layers of Example 1 and Comparative Example 1 were operated to measure the output characteristics (current-voltage characteristics). FIG. 11 is a graph showing the results. The horizontal and vertical axes of the graph respectively indicate the voltage and current density generated between the positive and negative electrode layers by the light irradiated to the power generation layer. Table 1 shows the power conversion efficiency (PCE) calculated from the graph of FIG. 11. The solar cell of Example 1 exhibits a higher output than the solar cell of Comparative Example 1. This is believed to be because the crystal grains in the power generation layer are enlarged with the intercalation of Rb, and the distribution density of the crystal grain boundaries is reduced, thereby reducing the loss of output current caused by carrier recombination at the crystal grain boundaries.

[0058] [Table 1]

[0059] [Evaluation of output characteristic stability 1] Xenon lamp, wavelength 100nm~1100nm, intensity 100W / cm 2The change in output characteristics over time was measured for the solar cells of Example 1 and Comparative Example 1 exposed to light. FIG. 12 is a graph showing the results. The horizontal and vertical axes of the graph indicate the measurement time and power conversion efficiency (PCE), respectively. The solar cell of Example 1 has a suppressed decrease in energy conversion efficiency compared to the solar cell of Comparative Example 1, and is able to maintain a high output. After 6000 seconds, the energy conversion efficiency of the solar cell of Comparative Example 1 drops to 64.53%, whereas the energy conversion efficiency of the solar cell of Example 1 is maintained at 88.5%. This is believed to be because the distribution density of the crystal grain boundaries in the power generation layer is low, preventing the penetration of light and suppressing deterioration of the power generation layer.

[0060] [Evaluation of output characteristic stability 2] 85℃ The time change in output characteristics was measured for the solar cells of Example 1 and Comparative Example 1 in a state where they were heated at 400° C. FIG. 13 is a graph showing the results. The horizontal and vertical axes of the graph are the same as those of FIG. 12. The solar cell of Example 1 has a suppressed decrease in energy conversion efficiency compared to the solar cell of Comparative Example 1, and is able to maintain a high output. After 1700 seconds, the energy conversion efficiency of the solar cell of Comparative Example 1 had dropped to 24.63%, whereas the energy conversion efficiency of the solar cell of Example 1 was maintained at 62.23%. This is believed to be because the distribution density of the crystal grain boundaries in the power generation layer is low, preventing the intrusion of heat and suppressing the deterioration of the power generation layer.

[0061] [Surface observation 2] The surfaces of the power generation layers formed in Example 2 and Comparative Example 2 were observed. 7 nm 2The SEM images are taken in an area of ​​(4800 nm × 3500 nm). In the power generation layer of Comparative Example 2, the crystal grain size is about 100 to 200 nm, whereas in the power generation layer of Example 2, the crystal grain size is about 1000 to 1500 nm, and the crystal size is significantly larger. The reason why the crystal grain size is larger in the power generation layer of Example 2 is thought to be because Rb is intercalated. However, pinholes are formed in the power generation layer of Example 2, and the characteristics may be inferior to those of the power generation layer of Example 1.

[0062] [Surface observation 3] The surfaces of the power generation layers formed in Example 3 and Comparative Example 2 were observed. 6 nm 2 The SEM images were taken in a region of (3100 nm × 2200 nm). In the power generation layer of Comparative Example 2, the crystal grain size was about 100 to 200 nm, whereas in the power generation layer of Example 3, the crystal grain size was about 500 to 1000 nm, and the crystal size was significantly larger. The larger crystal grain size in the power generation layer of Example 3 is believed to be due to Rb being intercalated.

[0063] [Evaluation of output characteristics 2] Solar cells including the power generation layers of Example 3 and Comparative Example 3 were operated to measure output characteristics (current-voltage characteristics). FIG. 18 is a graph showing the results. The horizontal and vertical axes of the graph are the same as those of FIG. 11. The power conversion efficiency (PCE) calculated from the graph of FIG. 18 is shown in Table 2. The solar cell of Example 3 exhibits a higher output than the solar cell of Comparative Example 3. This is believed to be because the crystal grains in the power generation layer are enlarged with the intercalation of Rb, and the distribution density of the crystal grain boundaries is reduced, thereby reducing the loss of output current caused by carrier recombination at the crystal grain boundaries.

[0064] [Table 2]

[0065] [Evaluation of the effect of the thickness of the first Rb supply layer on output characteristics] The solar cells including the power generation layers of Examples 1, 4, and 5 were operated, and the output characteristics (current-voltage characteristics) were measured. FIGS. 19 and 20 are graphs comparing the results. The graph of FIG. 19 shows the distribution of energy conversion efficiency corresponding to the thickness of the first Rb supply layer. The horizontal axis of the graph shows the thickness of the first Rb supply layer, and the vertical axis of the graph shows the energy conversion efficiency. The graph of FIG. 20 shows the measurement results of the current-voltage characteristics. The horizontal and vertical axes of the graph are the same as those of FIG. 11. The power conversion efficiency (PCE) calculated from the graph of FIG. 20 is shown in Table 3. Since the current-voltage characteristics and energy conversion efficiency obtained in Examples 1 and 4 are higher than those in Example 5, it is considered that the optimal range of the thickness of the first Rb supply layer is about 5 to 10 nm.

[0066] [Table 3]

[0067] [Evaluation of the effects of the first and second Rb supply layers on output characteristics] The solar cells having the power generation layers of Example 6 and Comparative Example 4 were operated, and the output characteristics (current-voltage characteristics) were measured. FIG. 21 is a graph comparing the results. The horizontal and vertical axes of the graph are the same as those of FIG. 11. The power conversion efficiency (PCE) calculated from the graph of FIG. 21 is shown in Table 4. The solar cell of Example 6 shows a higher output than the solar cell of Comparative Example 4. This is considered to be because the crystal grains in the power generation layer are enlarged with the intercalation of Rb, and the distribution density of the crystal grain boundaries is reduced, thereby reducing the loss of output current caused by carrier recombination at the crystal grain boundaries. Compared to the case where only the first Rb supply layer is formed, the output characteristics are further improved. This is considered to be because the effect of enlarging the crystal grains in the power generation layer is increased by the intercalation of Rb from multiple directions (two directions, above and below).

[0068] [Table 4]

[0069] [Evaluation of the effect of perovskite layer thickness on output characteristics] The solar cells having the power generation layers of Examples 1 and 7 to 9 were operated, and the output characteristics (current-voltage characteristics) were measured. Figures 22 and 23 are graphs comparing the results. The graph of Figure 22 shows the distribution of energy conversion efficiency corresponding to the thickness of the perovskite layer. The horizontal axis of the graph shows the thickness of the perovskite layer, and the vertical axis of the graph shows the energy conversion efficiency. The graph of Figure 23 shows the measurement results of the current-voltage characteristics. The horizontal and vertical axes of the graph are the same as those of Figure 11. The energy conversion efficiency (PCE) calculated from the graph of Figure 23 is shown in Table 5. The current-voltage characteristics and the energy conversion efficiency are high in all of Examples 1 and 7 to 9, but are particularly outstandingly high in Example 1. From this result, it can be seen that the optimal thickness of the perovskite layer is about 450 nm.

[0070] [Table 5]

[0071] [Evaluation of the effect of heating conditions on output characteristics] Solar cells equipped with the power generation layers of Examples 1 and 10 to 15 were operated, and output characteristics (current-voltage characteristics) were measured. FIG. 24 is a graph comparing the results of Examples 1 and 10 to 12. The horizontal axis of the graph indicates the heating temperature, and the vertical axis of the graph indicates the energy conversion efficiency. FIG. 25 is a graph comparing the results of Examples 1 and 13 to 15. The horizontal axis of the graph indicates the heating time, and the vertical axis of the graph indicates the energy conversion efficiency. The energy conversion efficiency is high in all of Examples 1 and 10 to 15, but is particularly outstandingly high in Example 1. From these results, it can be seen that the optimum heating temperature is about 140° C., and the optimum heating time is about 45 minutes. [Industrial Applicability]

[0072] The solar cell and its manufacturing method of the present invention provide a technology for intercalating Rb into the perovskite layer, and can be applied to various technical fields such as perovskite-type solar cells, light-emitting diodes (LEDs), catalysts, photodetectors, sensors, and energy storage devices. [Explanation of symbols]

[0073] 100...Solar cells 101...Base material 101a: One side of the substrate 102...electron transport layer 103 Power generation layer 103A...A site 103B B Site 103C...grain boundary 103X...X site 104...Hole transport layer 105...electrode layer 106 Negative electrode layer 107...First Rb supply layer 108...Perovskite layer 108a...Underside of the perovskite layer 108b Top surface of the perovskite layer 109...Second Rb supply layer

Claims

1. a laminate in which an electron transport layer, a power generation layer, and a hole transport layer are laminated in this order, or a hole transport layer, a power generation layer, and an electron transport layer are laminated in this order; a negative electrode layer connected to the electron transport layer; a positive electrode layer connected to the hole transport layer, A solar cell, wherein the power generation layer has a perovskite crystal structure, contains Rb, and the average grain size of crystal grains contained in the power generation layer is 350 nm or more.

2. 2. The solar cell according to claim 1, further comprising an Rb supply layer made of a halide of Rb, at least either between the power generation layer and the electron transport layer or between the power generation layer and the hole transport layer.

3. a first Rb supply layer forming step of forming a first Rb supply layer made of a halide of Rb on the electron transport layer or the hole transport layer; a perovskite layer forming step of forming a perovskite layer having a perovskite type crystal structure on the first Rb supply layer; and a heating step of heating the first Rb supply layer and the perovskite layer.

4. The method for manufacturing a solar cell according to claim 3 , wherein the first Rb supply layer is formed by a vapor deposition method.

5. The method further includes a second Rb supply layer forming step between the perovskite layer forming step and the heating step, 4. The method for manufacturing a solar cell according to claim 3, wherein in the second Rb supply layer forming step, a second Rb supply layer made of a halide of Rb is formed on the perovskite layer.

6. a perovskite layer forming step of forming a perovskite layer having a perovskite type crystal structure on the electron transport layer or the hole transport layer; a second Rb supply layer forming step of forming a second Rb supply layer made of a halide of Rb on the perovskite layer; and a heating step of heating the second Rb supply layer and the perovskite layer.

7. 7. The method for manufacturing a solar cell according to claim 5, wherein the second Rb supply layer is formed by using a vapor deposition method.